The Effectiveness of the Implementation of the Family Hope Program in North Sinjai District - Abd. Wahid; Juanda Nawawi; Nurlina Nurlina (Jurnal Office, 2021)
The Family Hope Program is a program initiated by the government of the Ministry of Social Affairs, where this program provides conditional non-cash assistance to Beneficiary Families. This study aims to determine the effectiveness of the implementation of the Family Hope Program (PKH) in North Sinjai District, Sinjai Regency. Collecting data in this study interviews and documentation. data were analyzed using qualitative analysis. The results showed that the effectiveness of the Family Hope Program in North Sinjai District, Sinjai Regency using 3 indicators of the effectiveness approach proposed by Martani and Lubis, namely the source approach, process approach and target approach. From some of these approaches, the results of the study show that it is less effective because the Integrated Data on Social Welfare (DTKS) of social assistance programs for the family of hope still uses old data, socialization and coordination of village officials and related parties are still lacking and in verifying commitment criteria Social welfare components are vulnerable. quite a long time, namely once a year. It is hoped that there will be an update of the Integrated Social Welfare Data a maximum of once every six months, there needs to be socialization and coordination between the Kelurahan apparatus and related parties as well as in verifying the commitment to the criteria for the PKH social welfare component, which is vulnerable every three months in order to find out the latest condition of the Beneficiary Family). Lack of socialization and coordination with village officials and related parties as well as in verifying the commitment of the criteria. The social welfare component has a relatively long time span, which is once a year. It is hoped that there will be an update of the Integrated Social Welfare Data a maximum of once every six months, there needs to be socialization and coordination between the Kelurahan apparatus and related parties as well as in verifying the commitment to the criteria for the PKH social welfare component, which is vulnerable every three months in order to find out the latest condition of the Beneficiary Family (KPM). lack of socialization and coordination with village officials and related parties as well as in verifying the commitment of the criteria. The social welfare component has a fairly long time span, which is once a year. It is hoped that there will be an update of the Integrated Social Welfare Data a maximum of every six months, there needs to be socialization and coordination between the Kelurahan apparatus and related parties as well as in verifying the commitment to the criteria for the social welfare component of PKH, which is vulnerable every three months in order to find out the current condition of the Beneficiary Families (KPM).